Removal of Mn(II) from Aqueous Solutions Using Bombax Malabaricum Fruit Shell Substrate - K. A. Emmanuel; K. A. Ramaraju; K. Somasekhara Rao (E-Journal of Chemistry)
Bombax Malabaricum carbon was found to have good sorption capacity for Mn(II) ion. Studies indicated that sorption of Mn(II) ion increases with increase in pH and a contact time of 50 min was found to be optimum. The effect of concentration slows that fruit shell substrate can remove Mn(II) ion. With the increase in the concentration of substrate the sorption also increases. The presence of Fe+2 and F- ions interfered with the adsorption of Mn(II) ion.